TOWARDS THE LANGUAGE AWARENESS ACTIVITIES IN THE SCHOOL CURRICULUM OF EASTERN LATVIA - Rimšāne, Inta; Svetlana, Ušča; Ežmale, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The present study discusses if the teachers who live and work in multicultural environment of Eastern Latvia and who are plurilingual themselves, are ready to use and integrate the new language awareness activities in the school curriculum. The paper reports on a survey carried out on over 30 teachers of the secondary school which is located in the rural territory called Malta, near the border with Russia. There are drawn the following conclusions: the teachers theoretically agree to the fact that the language awareness activities should be a part of the school curriculum. The activities should be integrated not only in the lessons of the foreign languages, but also in other subjects. However, the majority of the teachers are not ready to use the activities in their own lessons. In grades 5-12, the usage of the innovative activities could be prevented and often stopped by the necessity to prepare the students for passing the state examinations in Grades 9 and 12. The results of the state examinations are closely related to the teachers’ professional assessment, so many teachers have no motivation to use the activities, and possible the innovations, in the learning process.